Pengimejan resonans magnet kefungsian: pemerolehan, analisis dan pentafsiran data - Ahmad Mazlim Yusoff; Mohd Harith Hashim; Mohd Mahadir Ayob; Iskandar Kassim (penerbit ukm, 2005)
Baseline functional magnetic resonance imaging (fMRI) study has been carried out in the Department of Radiology, Universiti Kebangsaan Malaysia Hospital on a 25 year-old healthy male subject using a 1.5 T magnetic resonance imaging(MRI) system. The study used the movement of the right- and left-hand fingers to stimulate neural activity in the cerebral cortices. The subject was instructed to repeatedly press his fingers against the thumb during the functional scan. A five-cycle active-rest paradigm was used with each cycle consisted of 20 series of measurements, respectively. The results showed that the activated brain region due to finger movements was the precentral gyrus covering the primary motor area. Brain activations were contralateral to the right and left hand finger movements. The active-state signal intensity was found to be higher than that of the resting-state. Analyses performed on several activated regions of interest (ROI) on several slices showed a significant difference (p < 0.05) between the active and resting state intensities for the statistical threshold values (Z) = 1.0 and 1.5. The difference in the two means of the active and resting states signal intensities on any particular slice for both Z values showed a higher activation magnitude in the right hemisphere that was when the subject moved his left fingers. The number of activated voxels was also found to be higher in the right hemisphere then in left hemisphere. The results supported the fact that for a right-handed person, the activated motor area on the right hemisphere of the brain during the left hand finger movement experienced a higher hemodynamic response as compared to the left hemisphere of the brain during the right hand finger movement. The hemodynamic response phenomenon observed in this study is discussed based on the dependent of the signal contrast to the blood oxygenation level (BOLD).